Uma narrativa histórica do Campus Maués/IFAM: as tessituras do ensino médio integrado e a formação omnilateral no contexto amazônico (2010-2019) - Coelho, Mariana de Oliveira (2025)
This research investigates the memory of the Maués Campus of the Federal Institute of Education, Science and Technology of Amazonas, located in the interior of Amazonas, with the aim of recording and preserving institutional memory. The theme emerged during the Postgraduate Program in Professional and Technological Education (ProfEPT), based on reflections on the History of Professional Education, its conceptual bases and how this modality arrived in Maués-AM. The study aimed to investigate the historical process of the Maués/IFAM Campus (2010-1019) based on the fabric of Integrated High School and omnilateral training in documents and practice, with an emphasis on preserving the memory of a Professional and Technological Education institution. The theoretical contribution was made by authors such as Manacorda (2007), Frigotto (2018), Della Fonte (2020) Ciavatta (2005), Ramos (2014), among others, who address topics such as Professional and Technological Education, Vocational High School and omnilateral training. The discussion involving memory and oral history as a source of research was based on Magalhães (2004), Le Goff (1990), Santos (2018), Halbwachs (2003), Silva and Barbosa (2022), Freitas ((2006), among others. This research was submitted to and approved by the Human Research Ethics Committee (CEPSH). The research site was the Maués/IFAM Campus and the participants included ten teachers who taught classes for Integrated High School and nine graduates who served as student representatives in the Integrated Technical courses in Agriculture, Information Technology and Administration. The methodological approach was qualitative, with an exploratory character. Data collection techniques involved documentary research and semi-structured interviews, based on thematic oral history. For data analysis, based on Moraes and Galiazzi (2020), Discursive Textual Analysis was chosen, which emphasizes the subjectivity, anchored in the world of experience and everyday life, resulted in the metatext entitled: “Campus Maués/IFAM as a place of memory and identity: a watershed for the Maués community regarding comprehensive human development”. The investigation revealed that the implementation of the Instituto Federal do Amazonas (IFAM) in Maués, with the proposal of Vocational High School Education, represented a crucial milestone for the community, by expanding access to free, quality public education, promoting social inclusion and contributing to the integral human development of students, articulating technical, scientific and cultural knowledge. The research highlights the importance of preserving institutional records, both physical and digital, to ensure that significant milestones are not lost, as well as the legacies of achievements of the people (teachers, technicians and students) who are part of the institution. All this safeguarding helps future generations to have knowledge of the past, understand the present and, at the same time, project the future more accurately, establishing a bond between generations and strengthening the identity of the institution. Based on this information, an Educational Product was developed in e-book format, entitled “The Tree of Knowledge: Maués/IFAM Campus as a Place of Memory and Identity”, a material that uses an analogy to tell the story of the Maués/IFAM Campus, correlating the constituent parts of a plant (guarana) with the fundamental parts of a successful school.